(untitled) (Research, Society and Development, 2022)
Protium heptaphyllum, known as amescla, amelcegueira and breu-branco, with wide national distribution, found especially in the Amazon and Atlantic Forest. It is a species rich in essential oil, but the use of resin as a medicine stands out. Therefore, this study aimed to survey the chemical variability between essential oils of Protium hepthaphylum from different locations. This is a systematic review in SciElo databases, PubMed and Google Scholar, with the search strategy descriptors "essential oil" and "Protium heptaphyllum" in Portuguese and English, published between 2000 and 2020. Ten articles were selected for analysis of the chemical profile and chemical variability of the essential oil of P. heptaphyllum, however, it was possible to survey 28 different chemical analysis for 10 different collection accessions. Of the 28 chemical analyses, 21 were carried out from oils extracted from the resin, 03 from leaves and 04 from fruits and a total of 145 substances were raised. The chemical variability of essential oils between each location was evident, with emphasis on 21 major substances. The monoterpene group was the most representative, especially limonene, α-terpineol, 1,8-cineole, p-cymene, α and β-phelandrene. It is possible to conclude that environmental changes may be responsible for this variability, not ruling out the possibility that some access is a chemotype.